KONTRIBUSI DAN PENGEMBANGAN USAHATANI BUNGA TERATAI TERHADAP TOTAL PENDAPATAN RUMAH TANGGA PETANI (Studi Kasus di Subak Saradan Desa Sibang Gede, Kecamatan Abiansemal, Kabupaten Badung) - Desak Nyoman Keristina Natalia; Dian Tariningsih; Utari Vipriyanti (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
Most Indonesians depend on agriculture, whether agriculture comes from the production process in rice fields, fields, farm farming or more broadly by breeding, searching for forest products, and the fishery sector. Horticultural subsectors are part of the agricultural sector that has the potential to be a source of economic growth in Indonesia. One of the horticultural plants that have high economic value is the flower plant (floriculture). Sibang village is a village that most of the population makes a living in the agricultural sector. One of the agricultural products in Sibang Gede Village is lotus flower. The location of this study is determined purposively i.e. the determination of the research location intentionally. The number of respondents in this study was 60 people. The data collection method in this study uses census method. Based on research data, lotus farming in Subak Saradan, Sibang Gede Village contributes 30.03 percent to the total household income of farmers, with the average income of lotus farming per one planting period Rp. 5,252,318. Lotus farming efficiency as measured by R/C ratio is 3.8. Thus, lotus cultivation in Sibang Gede Village is profitable and worth developing. Based on this, the Badung Regency Government plans the development of Agrotourism Jogging Track tourism in the Subak Saradan area because the potential of tourist attractions in subak consists of natural beauty, agricultural commodities, and ritual activities that can attract the interest of the public